Peningkatan Kapasitas UMKM Dalam Penerapan e-Accounting Siapik dan e- Tax Coretax Di Umkm Desa Banjarwangi Kab. Bogor - Ayi Jamaludin Aziz; Ade Budi Setiawan; Chandra Ayu Pramestidewi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Banjarwangi Village, Bogor Regency, still face challenges in financial management and tax reporting due to low literacy and limited use of digital technology. This community service program aims to enhance MSME capacity through the implementation of SIAPIK e-Accounting and Coretax e-Tax. The program was conducted using a participatory approach consisting of preparation and coordination, initial condition assessment, training and socialization, implementation assistance, and evaluation. The activity involved 10 active MSMEs out of 20 invited participants. The results indicate an improvement in MSMEs’ understanding and skills in digital financial recording and tax administration. Technology acceptance evaluation using the Technology Acceptance Model (TAM) shows positive perceptions of ease of use and usefulness, along with behavioral intention and actual use of the applications. This program contributes to improving MSMEs’ financial and tax literacy and supports the strengthening of sustainable business governance.